Manajemen Perpustakaan Dalam Membentuk Budaya Literasi Santri Di Yayasan Miftahut Thullab Kedungdung - Farida, Siti; Al-Basuni, Faisol (AL -ALLAM, 2023)
Management is a science whose existence is very important, because the science of management studies the art of managing, the art of relating and working with others and the art of leadership. Islamic boarding schools are one of the educational institutions that are able to give birth to generations of nations who have competitiveness in terms of education, because education will be a benchmark for the development and progress of a country. Therefore Islamic boarding schools are also required to provide varied education through institutional units, one of which is the library. The focus of this research is how to plan library management at the Miftahut Thullab foundation in shaping student literacy, how to implement library management in shaping student literacy at the Miftahut Thullab foundation , how to evaluate library management in shaping student literacy at the Miftahut Thullab foundation. Therefore, this study aims to see how the management is carried out by the library and the effectiveness of the literacy program presented by the library in shaping student literacy at the Miftahut Thullab foundation. This research uses a qualitative approach with a phenomenological type. while data collection techniques using interviews, observation and documentation. The object of research here is the Gedangan Islamic Boarding School including leaders, principals, teachers, library managers, and students at the Miftahut Thullab foundation. The results of this study indicate that the management planned in the library has been regulated and in accordance with the needs of the library, and in library management focused on literacy culture in view of the objectives and the development process carried out at the Miftahut Thullab foundation library, as well as evaluations carried out for each component related to the library.